C-reactive protein, chemerin, fetuin-A and osteopontin as predictors of cardiovascular risks in persons with psoriasis vulgaris - Borsky, P; Fiala, Z; Andrys, C; Beranek, M; Hamakova, K; Kremlacek, J; Malkova, A; Svadlakova, T; Krejsek, J; Palicka, V; Rehacek, V; Kotingova, L; et al. (Physiological research, 2021)
The study aimed to contribute to understanding the role of CRP, chemerin, fetuin-A and osteopontin and to assess their suitability as biomarkers of early stages of cardiovascular diseases in psoriasis vulgaris. Serum levels measured in 28 patients and 22 controls. Patients: increased levels of CRP (p<0.001), chemerin (p<0.05), osteopontin (p<0.05) and decreased levels of fetuin-A (p<0.05), significant relationships between CRP and fetuin-A (rho=0.530, p<0.01), CRP and chemerin (rho=0.543, p<0.01), CRP and age (rho=0.590, p<0.001), osteopontin and fetuin-A (r=-0.415, p<0.05), chemerin and PASI score (rho=-0.424, p<0.05). We confirmed specific roles of the biomarkers in psoriasis. CRP, fetuin-A and osteopontin could be considered appropriate markers for the detection of early stages of cardiovascular diseases.
Keywords: alpha-2-HS-Glycoprotein; Male; Chemokines; biologické markery; osteopontin; psoriáza; Biomarkers; Heart Disease Risk Factors; Adult; fetuin A; C-reaktivní protein; Osteopontin; Case-Control Studies; dospělí; mužské pohlaví; lidé; Psoriasis; ženské pohlaví; studie případů a kontrol; Humans; Body Mass Index; index tělesné hmotnosti; C-Reactive Protein; rizikové faktory kardiovaskulárních chorob; Female; lidé středního věku; chemokiny; Middle Aged